Global population exposure to landscape fire air pollution from 2000 to 2019 - Xu, Rongbin; Ye, Tingting; Yue, Xu; Yang, Zhengyu; Yu, Wenhua; Zhang, Yiwen; Bell, Michelle L.; Morawska, Lidia; Yu, Pei; Zhang, Yuxi; Wu, Yao; Liu, Yanming; et al. (Nature (London), 2023)
Wildfires are thought to be increasing in severity and frequency as a result of climate change 1 – 5 . Air pollution from landscape fires can negatively affect human health 4 – 6 , but human exposure to landscape fire-sourced (LFS) air pollution has not been well characterized at the global scale 7 – 23 . Here, we estimate global daily LFS outdoor fine particulate matter (PM 2.5 ) and surface ozone concentrations at 0.25° × 0.25° resolution during the period 2000–2019 with the help of machine learning and chemical transport models. We found that overall population-weighted average LFS PM 2.5 and ozone concentrations were 2.5 µg m −3 (6.1% of all-source PM 2.5 ) and 3.2 µg m −3 (3.6% of all-source ozone), respectively, in 2010–2019, with a slight increase for PM 2.5 , but not for ozone, compared with 2000–2009. Central Africa, Southeast Asia, South America and Siberia experienced the highest LFS PM 2.5 and ozone concentrations. The concentrations of LFS PM 2.5 and ozone were about four times higher in low-income countries than in high-income countries. During the period 2010–2019, 2.18 billion people were exposed to at least 1 day of substantial LFS air pollution per year, with each person in the world having, on average, 9.9 days of exposure per year. These two metrics increased by 6.8% and 2.1%, respectively, compared with 2000–2009. Overall, we find that the global population is increasingly exposed to LFS air pollution, with socioeconomic disparities. The global population is increasingly exposed to daily landscape fire-sourced air pollution but there are socioeconomic disparities, with this pollution four times higher in low-income countries than in high-income countries during the period 2000–2019.